Ketoksikan Akut dari Ekstrak Etanolik Daun Jarak Pagar (Jatropa curcas) pada Mencit Jantan Galur Balb/C - Baroroh, Hanif Nasiatul; Nur Rachmani, Eka Prasasti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
The acute toxicity of Jatropa curcas leaves on Balb/C male mice was studied in rats. This research aimed to determine acute toxicity, evaluate spectrum of toxic effect and mechanism that caused the death of animal test after administration of ethanolic extract of J. curcas leaves, single dosage orally on 24 hours observation. The research used male mice, which are divided into 5 groups. Group I was negative control with CMC-Na. Group II, III, IV, and V were given extract with dose of 1400 mg/kgBW, 2240 mg/kgBW, 3584 mg/kgBW and 5734 mg/kgBW, respectively. Evaluation of the toxic symptoms and death of animal test was done for 24 hours. If the animal test was died before 24 hours then it underwent surgery to take the heart, liver, lung, and kidney. In the end of the evaluation, all mice were killed to take the vital organs for histopathologic examination. No mortality was observed during study. The test resulted LD50 of ethanolic extract from J. curcas leaves using Balb/C male mice was 5734 mg/kg of BW. It was categorized as practically not toxic. Administration of the extract did not cause alterations of animal behaviours. Histopathology examination shows inflammation in lung, liver, and kidney after administration of the extract.